Water hyacinth in Africa and the Middle East : a survey of problems and solutions - Navarro, L. A. (Luis A.); Kanyama-Phiri, George Yobe (IDRC, 2000)
Freshwater infestation by the water hyacinth weed has reached crisis proportions in many areas of Africa and the Middle East. Accumulated environmental, economic, and social damages to date are estimated in the billions of dollars. Most severely affected are riparian communities and those people who depend upon the environmental services or production from affected water bodies. Years of research has produced significant new findings and advances in water hyacinthcontrol and utilization. However, it is all too apparent that this knowledge is not being properly applied to manage the weed. Early.